2017
DOI: 10.1126/scisignal.aag2791
|View full text |Cite
|
Sign up to set email alerts
|

Retrograde signaling from autophagy modulates stress responses

Abstract: Macroautophagy is a process in which cytoplasmic components, including whole organelles, are degraded within lysosomes. Basally, this process is essential for homeostasis and is constitutively functional in most cells, but it can also be implemented as part of stress responses. We discuss findings showing that autophagy proteins can modulate and amplify the activities of transcription factors involved in stress responses, such as those in the p53, FOXO, MiT/TFE, Nrf2, and NFkB/Rel families. Thus, transcription… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
41
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 111 publications
1
41
1
Order By: Relevance
“…MDC staining and TEM both displayed the ultrastructural features of autophagy in these cells ( Figure 3 a,b). The results of genes showed that the expression of Atg 5, Atg 7, and beclin-1 was increased after treating with 20(S)-GRh2 in U937 and K562 cells ( Figure 3 c), and were consistent with the previous studies [ 53 , 54 , 55 ]. LC3, which is a recognized indicator of autophagy evaluation and measurement, is widely used by many autophagy researchers.…”
Section: Discussionsupporting
confidence: 91%
“…MDC staining and TEM both displayed the ultrastructural features of autophagy in these cells ( Figure 3 a,b). The results of genes showed that the expression of Atg 5, Atg 7, and beclin-1 was increased after treating with 20(S)-GRh2 in U937 and K562 cells ( Figure 3 c), and were consistent with the previous studies [ 53 , 54 , 55 ]. LC3, which is a recognized indicator of autophagy evaluation and measurement, is widely used by many autophagy researchers.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, Res induced autophagy partially through ROS. AMPK-mTOR is a classic regulatory signaling pathway in autophagy (34). However, in the experiments performed in the present study, Res did not affect AMPK and mTOR, indicating that Res induced non-classical autophagy.…”
Section: Discussioncontrasting
confidence: 69%
“…Depending on the context, it can also inhibit autophagy. 84,85 As there are a growing number of studies in autophagy and its cytoprotective effect, there might be a chance to help cancer therapeutic approaches with agents that inhibit autophagy. 86,87…”
Section: Change Of Autophagy Pathwaysmentioning
confidence: 99%